'Just a GP': a mixed method study of undermining of general practice as a career choice in the UK. Issue 11 (3rd November 2017) - Alberti, Hugh; Banner, Kimberley; Collingwood, Helen; Merritt, Kymberlee
Abstract : Objectives: Failure to recruit sufficient applicants to general practice (GP) training has been a problem both nationally and internationally for many years and undermining of GP is one possible contributing factor. The aim of our study was to ascertain what comments, both negative and positive, are being made in UK clinical settings to GP trainees about GP and to further explore these comments and their influence on career choice. Methodology: We conducted a mixed methods study. We surveyed all foundation doctors and GP trainees within one region of Health Education England regarding any comments they experienced relating to a career in GP. We also conducted six focus groups with early GP trainees to discuss any comments that they experienced and whether these comments had any influence on their or others career choice. Results: Positive comments reported by trainees centred around the concept that choosing GP is a positive, family-focused choice which facilities a good work–life balance. Workload was the most common negative comment, alongside the notion of being 'just a GP'; the belief that GP is boring, a waste of training and a second-class career choice. The reasons for and origin of the comments are multifactorial in nature. Thematic analysis of the focus groups identified key factors such as previous exposure to and experience of GP, family members who were GPs, GP role models, demographics of the clinician and referral behaviour. Trainees perceived that negative comments may be discouraging others from choosing GP as a career. Conclusion: Our study demonstrates that negative comments towards GP as a career do exist within clinical settings and are having a potential impact on poor recruitment rates to GP training. We have identified areas in which further negative comments could be prevented by changing perceptions of GP as a career. Additional time spent in GP as undergraduates and postgraduates, and positive GP role models, could particularly benefit recruitment. We recommend that undermining of GP as a career choice be approached with a zero-tolerance policy.